2012
DOI: 10.1007/s13197-012-0817-6
|View full text |Cite
|
Sign up to set email alerts
|

Zebra blenny (Salaria basilisca) viscera as a source of solvent-stable proteases: characteristics, potential application in the deproteinization of shrimp wastes and evaluation in liquid laundry commercial detergents

Abstract: The present study describes the characterization of crude protease extract from zebra blenny (Salaria basilisca) and its evaluation in liquid detergent and shrimp waste deproteinization. At least five caseinolytic proteases clear bands were observed in zymogram. The crude alkaline protease showed optimum activity at pH 8.0 and 60°C, and it was highly stable over a wide range of pH from 6.0 to 11.0. Proteolytic enzymes showed extreme stability towards non-ionic surfactants (5 % Tween 80 and 5 % Triton X-100) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…However, the crude enzyme was partially inhibited by Ba 2+ , Cu 2+ ; and strongly affected by Mn 2+ , Hg 2+ , and Zn 2+ , suggesting the adverse effect of heavy metal ions on the crude protease. A similar result was observed by Ktari et al (2012a), who showed that only Ca 2+ increased enzyme activity of crude enzyme extract from zebra blenny viscera (119%); whereas, Cu 2+ , Hg 2+ , and Zn 2+ strongly affected the proteolytic activity of the crude enzyme extract.…”
Section: Effects Of Various Enzyme Inhibitors and Metal Ions On Protesupporting
confidence: 86%
See 1 more Smart Citation
“…However, the crude enzyme was partially inhibited by Ba 2+ , Cu 2+ ; and strongly affected by Mn 2+ , Hg 2+ , and Zn 2+ , suggesting the adverse effect of heavy metal ions on the crude protease. A similar result was observed by Ktari et al (2012a), who showed that only Ca 2+ increased enzyme activity of crude enzyme extract from zebra blenny viscera (119%); whereas, Cu 2+ , Hg 2+ , and Zn 2+ strongly affected the proteolytic activity of the crude enzyme extract.…”
Section: Effects Of Various Enzyme Inhibitors and Metal Ions On Protesupporting
confidence: 86%
“…1173-3038, Sfax, Tunisie. E-mail: ibkhairia@yahoo.com 1 Downloaded by [University of Otago] at 07:07 28 July 2015 a largely studied group of enzymes because of their wide use in many industrial applications such as food (Handel et al, 1995), pharmaceuticals and leather (Rao et al, 1998), peptide synthesis (Kumar and Takagi, 1999), shrimp waste deproteinization (Ktari et al, 2012a), enzymatic descaling of fish (Gildberg, 1994), and with a two-thirds share in the detergent industry alone (Kumar and Takagi, 1999). In general, enzyme technology has evolved to become an integral part of the food, detergent, and medical industries.…”
Section: Introductionmentioning
confidence: 99%
“…Staining of protease and lipase activities was performed on SDS-PAGE, according to Ktari et al (2014), emphasizing not to heat the enzymes before electrophoresis. Electrophoresis condition was set as the mention above.…”
Section: Detection Of Protease and Lipase Activities By Zymographymentioning
confidence: 99%
“…Technological development in detergent industries has allowed subtilisins, a protease enzyme from Bacillus subtilis, as additive. However, Ktari et al (2014) stated that this enzyme is not ideal for detergent since it has not fulfilled specific criteria as detergent additive viz. low thermal stability and short shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…Residual activity was determined at 45C using 0.5% casein as substrate according to Ktari et al (2014 The crud alkaline protease was mixed with ammonium sulfate at 20%, 40% and 60% saturation. The mixture was incubated at 4C for 24hrs.…”
Section: Determination Of Ph Stabilitymentioning
confidence: 99%